2019
DOI: 10.1002/dvdy.15
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and postembryonic development of the ornamental twin‐tail goldfish

Abstract: Background Twin‐tail ornamental goldfish have “bifurcated median fins,” a peculiar morphology known to be caused by a mutation in the chdA gene. However, several ambiguities regarding the development of the phenotype remain due to a paucity of detailed observations covering the entire developmental timeframe. Results Here, we report a detailed comparative description of embryonic and postembryonic development for two representative twin‐tail o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
2
26
1
Order By: Relevance
“…Therefore, accurate staging required the use of additional features and indices such as brain partitioning, formation of optic bud and OVC. 17,22,34 The development of the brain rudiment and optic bud were comparable to those reported for zebrafish. 17 Unlike the application of OVC in goldfish 22 and OVL in zebrafish 17 to stage pharyngula, they were more useful for staging segmentation in G. holbrooki.…”
Section: Establishment Of the Developmental Staging System Of The G Holbrookisupporting
confidence: 75%
See 3 more Smart Citations
“…Therefore, accurate staging required the use of additional features and indices such as brain partitioning, formation of optic bud and OVC. 17,22,34 The development of the brain rudiment and optic bud were comparable to those reported for zebrafish. 17 Unlike the application of OVC in goldfish 22 and OVL in zebrafish 17 to stage pharyngula, they were more useful for staging segmentation in G. holbrooki.…”
Section: Establishment Of the Developmental Staging System Of The G Holbrookisupporting
confidence: 75%
“…Maintaining a uniform temperature is vital for standardization of development. 17,23,32,34 (2) To account for the timing of fertilization, mating was used as a proxy as suggested for G. affinis. 2 In platyfish and swordtail, the duration of gestation is 28 days and mature ova can be fertilized after 7 days.…”
Section: Establishment Of the Developmental Staging System Of The G Holbrookimentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, at the late larval stages, dorsal fin rays were not observed in group 1 individuals, dorsal fin rays were missing at several body levels in group 2 individuals, and dorsal fin rays were completely developed in the group 3 individuals (Fig. 3i-n) 16,21 . This concordance of phenotypes suggested that chdS wt mRNA at the early embryonic developmental stage influences the eventual skeletal morphology of the dorsal fin (Fig.…”
Section: S5)mentioning
confidence: 98%